Pengembangan Media Pembelajaran Pendidikan Agama Islam dan Budi Pekerti Berbasis Web Kelas XIPA di SMAN 1 Enrekang - Firqa Najiah, Nur; Fakhrunnisaa, Nur; Assafari, Amir Faqihuddin (ISLAMIKA, 2024)
This research discusses the development of web learning of Islamic Religious Education and ethics subjects based on web class X IPA at SMAN 1 Enrekang to determine the level of validity of this product. This type of research is R&D (Research and Development) research using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Students of X MIPA VI class of SMAN 1 Enrekang will be the subject of the research. Data collection techniques were obtained through documentation, interviews, and questionnaires. The data were analyzed using a process called quantitative descriptive analysis. The research results of web learning developed by researchers obtained validation results from media experts as much as 94%, with a classification of "very valid", subject teacher validation as much as 88.55% with a classification of "very valid", and material expert validation as much as 91.19% with a classification of "very valid". And the level of practicality by students was 91.3% which was included in the "very practical" classification. According to these results, it can be concluded that web learning in the subject of Islamic Religious Education and web-based ethics using google sites for class X IPA at SMAN 1 Enrekang is feasible to use as learning media.